Numerical solution for the thermally insulated cracks in bonded dissimilar materials using hypersingular integral equations - Hamzah, K. B.; Nik Long, N. M. A.; Senu, N.; Eshkuvatov, Z. K. (Elsevier, 2021)
The new system of hypersingular integral equations (HSIEs) for the thermally insulated inclined cracks and thermally insulated circular arc cracks subjected to remote shear stress in bonded dissimilar materials was formulated by using the modified complex potentials (MCPs) function method with the continuity conditions of the resultant force, displacement and heat conduction functions. This new system of HSIEs is derived from the elasticity problem and heat conduction problem by using crack opening displacement (COD) function and temperature jump along the crack faces. The appropriate quadrature formulas were used to solve numerically the new system of HSIEs for the unknown COD function and the known traction along the crack as the right hand term. Numerical solutions for the value of nondimensional stress intensity factors (SIFs) at all the cracks tips are illustrated. The comparison of nondimensional SIFs for the cracks with and without thermal is also illustrated.